Permanent deformation investigation of rubber polymer modified binder in superpave hot mix asphalt mixture - Putra Jaya, Ramadhansyah; Ekarizan, Shaffie; Ahmad Kamil, Arshad; K. A., Masri; Wardati, hashim (Universiti Teknologi MARA, 2020)
Moisture susceptibiltiy is one of the common types of pavement failure found in asphaltic pavements. Climatic factor such as temperature and moisture has a profound effect on the durability of hot mix asphalt pavements. Couple with high traffic loads/stresses made stripping of pavement materials inevitable. Thus, it has become necessary to improve the efficiency of the design of hot mix asphalt (HMA) for better performance and safe riding comfort. This study investigates and discusses the findings on the stripping performance of dense graded Superpave mixes using two type of binder; un-modified binder and rubber polymer modified binder (RPM) using Superpave mix design (AASHTO TP4) procedure. The RPM binder consists of 4% of both rubber crumb and EVA polymer. Modified Lottman and Resilient Modulus tests were used to evaluate the stripping performance in these mixtures and this study also documents the effect of different temperature on tensile strength ratio (TSR) and resilient modulus ratio (RMR) on the HMA mixtures. Experimental evidences show that the RPM binder mixes were found to have significantly improved the resistance to moisture damage compared to unmodified binder mixtures. The RPM binder application may able to alleviate problems related to aggregate stripping and potholes on our road. Statistical analysis showed good correlation between resilient modulus and tensile strength ratio.